2007
DOI: 10.1021/cm070593d
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Mullite and Spinel Phases from SiO2−Al2O3 Gels Prepared by a Spray Pyrolysis Technique. A 29Si and 27Al MAS NMR Study

Abstract: Thermal behavior of alumino-silicate gels prepared by spray pyrolysis, with Al/Si ratios between 1.5 and 18, has been analyzed by differential thermal analysis (DTA), X-ray diffraction, transmission electron microscopy, IR, and 29Si and 27Al magic angle spinning NMR techniques. In samples heated at 800 °C, tetra-, penta-, and octahedral aluminum were detected. In samples heated at 900 °C, Al-rich mullite (Al/Si = 4−6) or Si-spinel nuclei (Al/Si = 10−18) are formed after the partial segregation of SiO2 from alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Earlier studies reported that (mullitetype) Al-rich aluminosilicates exhibit more intense octahedral than tetrahedral Al resonance, whereas in high Si samples, more tetrahedral than octahedral Al is present. 41,46 These findings are consistent with the XRF results (Table I), in which the clay-based waste was observed to be higher in Si than Al.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Earlier studies reported that (mullitetype) Al-rich aluminosilicates exhibit more intense octahedral than tetrahedral Al resonance, whereas in high Si samples, more tetrahedral than octahedral Al is present. 41,46 These findings are consistent with the XRF results (Table I), in which the clay-based waste was observed to be higher in Si than Al.…”
Section: Resultssupporting
confidence: 89%
“…The fact that Al(VI) generated a much less intense signal than Al(IV) is an indication that the SW waste contained a large proportion of amorphous aluminosilicates higher in Si than in Al. Earlier studies reported that (mullite‐type) Al‐rich aluminosilicates exhibit more intense octahedral than tetrahedral Al resonance, whereas in high Si samples, more tetrahedral than octahedral Al is present . These findings are consistent with the XRF results (Table ), in which the clay‐based waste was observed to be higher in Si than Al.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…27 Al MAS-NMR spectra from the activated fly ash displayed four signals centred at +57.2, +49.4, +0.9 and −7.5 ppm. The former two signals were associated to Al T in the N-A-S-H gel and in the anhydrous fly ash, respectively, while the latter two signals to octrahedral aluminum in mullite [54]. The analysis of the activated mixtures confirmed that the amount of the anhydrous slag declined with an increase of the percentage of the fly ash, while the amount of the anhydrous fly ash and mullite grew, see Table 4.…”
Section: Resultsmentioning
confidence: 95%